DNA Damage Induced by Methylated Trivalent Arsenicals Is Mediated by Reactive Oxygen Species - Nesnow, Stephen; Roop, Barbara C; Lambert, Guy; Kadiiska, Maria; Mason, Ronald P; Cullen, William R; Mass, Marc J (Chemical research in toxicology, 2002)
Arsenic is a human carcinogen; however, the mechanisms of arsenic's induction of carcinogenic effects have not been identified clearly. We have shown previously that monomethylarsonous acid (MMAIII) and dimethylarsinous acid (DMAIII) are genotoxic and can damage supercoiled φX174 DNA and the DNA in peripheral human lymphocytes in culture. These trivalent arsenicals are biomethylated forms of inorganic arsenic and have been detected in the urine of subjects exposed to arsenite and arsenate. We show here by molecular, chemical, and physical methods that reactive oxygen species (ROS) are intermediates in the DNA-damaging activities of MMAIII and DMAIII. Using the φX174 DNA nicking assay we found that the ROS inhibitors Tiron, melatonin, and the vitamin E analogue Trolox inhibited the DNA-nicking activities of both MMAIII and DMAIII at low micromolar concentrations. The spin trap agent 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) also was effective at preventing the DNA nicking induced by MMAIII and DMAIII. ESR spectroscopy studies using DMPO identified a radical as a ROS intermediate in the DNA incubations with DMAIII. This radical adduct was assigned to the DMPO-hydroxyl free radical adduct on the basis of comparison of the observed hyperfine splitting constants and line widths with those reported in the literature. The formation of the DMPO-hydroxyl free radical adduct was dependent on time and the presence of DMAIII and was completely inhibited by Tiron and Trolox and partially inhibited by DMSO. Using electrospray mass spectrometry, micromolar concentrations of DMAV were detected in the DNA incubation mixtures with DMAIII. These data are consistent with the conclusions that the DNA-damaging activity of DMAIII is an indirect genotoxic effect mediated by ROS-formed concomitantly with the oxidation of DMAIII to DMAV.